Donor Monoclonal Gammopathy May Cause Lymphoproliferative Disorders in Solid Organ Transplant Recipients. Issue 9 (5th May 2016) - Felldin, M.; Ekberg, J.; Polanska‐Tamborek, D.; Hansson, U.; Sender, M.; Rizell, M.; Svanvik, J.; Mölne, J.
Abstract : Prior research on donor monoclonal gammopathy of undetermined significance (MGUS) has been inadequate regarding the risk for lymphoproliferative disease in solid organ transplantation recipients. Seven organ recipients from two different donors developed lymphoproliferative disease. The origin of the malignancy was determined by use of microsatellite analysis, and the plasma of the two donors was analyzed with the use of electrophoresis. The clinical courses of the seven recipients were followed for 36–60 months. One donor transmitted lymphoplasmacytic lymphoma to two kidney recipients and MGUS to a liver recipient, all IgMκ. A second donor caused IgGλ myeloma in two kidney and one liver recipient, and IgGλ gammopathy in a heart recipient. Transplant nephrectomy was performed in three kidney recipients and remission was achieved. The fourth kidney recipient has kept the graft and the disease has progressed. The liver recipient died from myeloma. There were no clinical signs of lymphoproliferative disease in the donors, but retrospective serum analyses showed M‐components, IgMκ (37 g/L) and IgGλ (8 g/L). Donors with MGUS may cause donor‐transmitted malignancies via passenger lymphocytes/plasma cells in solid organ recipients. The results call for a large register study of the incidence of donor MGUS and lymphoproliferative disease in their recipients. Abstract : Two donors with unknown gammopathy transmitted lymphoproliferative disorders to seven solid organ recipients.